Selective and reversible 1,3-dipolar cycloaddition of 6-aryl-1,5-diazabicyclo[3.1.0]hexanes with 1,3-diphenylprop-2-en-1-ones under microwave irradiation - Molchanov, Alexander P.; Efremova, Mariia M.; Kryukova, Mariya A.; Kuznetsov, Mikhail A. (Beilstein Journal of Organic Chemistry, 2020)
The first example of the cycloaddition of in situ-generated azomethine imine under microwave conditions is described. The reaction of 6-aryl-1,5-diazabicyclo[3.1.0]hexanes with 1,3-diphenylprop-2-en-1-ones proceeds regio- and stereoselectively giving mostly good yields of the corresponding perhydropyrazolopyrazoles. The products of the reaction undergo cycloreversion under the reaction conditions.
Keywords: azomethine imines; cycloaddition; diazabicyclohexanes; diaziridines; regioselectivity